Rancang Bangun Pendeteksi Kebakaran Dan Monitoring Berbasis IoT Dengan Microcontroller NodeMCU - Arafa Sudarta; Ferdiansyah Ferdiansyah; Rimhot Richson Siahaan; Maruloh Maruloh (Bahasa Indonesia, 2022)
In general, every house or shop has the possibility of experiencing a fire, which is caused by many factors. We need a fire detection tool that will notify the building owner so that it can be handled early and effectively. In this research, an Internet of Things Based Fire Detector Design will be made using the NodeMCU Microcontroller to detect fire and smoke to determine the occurrence of a fire using an IR Flame Sensor[1] and MQ-2 Sensor[2], [4], where the input data comes from reading the sensor value and the data is sent to the cloud service platform. thinger.io and the data is displayed in live monitoring. From the design made, the results obtained from the IoT-Based Fire Detector Design Using the NodeMCU Microcontroller to detect fire and smoke to determine the occurrence of fires.